Bifidobacterium lactis BL-99 protects mice with osteoporosis caused by colitis via gut inflammation and gut microbiota regulation. Issue 3 (21st January 2022) - Lan, Hui; Liu, Wei-Hsien; Zheng, Hanying; Feng, Haotian; Zhao, Wen; Hung, Wei-Lian; Li, Hongwei
Abstract : Bifidobacterium lactis BL-99 intervention has a protective effect on osteoporosis caused by colitis induced by DSS, partially through changes in the gut microbiota and a decrease in inflammatory factors. Abstract : Patients diagnosed with inflammatory bowel disease or related conditions also frequently suffer from osteoporosis as a consequence of changes in the intestinal microenvironment and consequent dysbiosis. We hypothesized that anti-inflammatory probiotic treatment would be sufficient to alleviate intestinal inflammation and thereby prevent the development of osteoporosis. To that end, the ability of Bifidobacterium lactis BL-99 administration to protect against bone loss in an experimental model of dextran sodium sulfate-induced ulcerative colitis (UC) was analyzed, and the underlying molecular mechanisms were interrogated in detail. The results of these analyses revealed that BL-99 administration suppressed colitis-associated weight loss ( P < 0.05), disease activity index scores, and the production of proinflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-17) ( P < 0.05). Colon tissue pathological sections similarly revealed BL-99-mediated reductions in tissue injury severity. Micro-computed tomography (Micro-CT) analyses further exhibited significant improvements in percent bone volume (BV/TV) as well as trabecular number and thickness in BL-99-treated animals ( P < 0.05). Such probiotic supplementation also resulted in pronounced changes in the composition of the gut microbiota. Moreover, BL-99 intervention markedly increased the expression of intestinal barrier-related proteins (Claudin-1, MUC2, ZO-1, and Occludin). Together, these results suggest that BL-99 can be utilized as a beneficial probiotic preparation to prevent the incidence of osteoporosis in UC patients owing to its ability to shape the intestinal microflora and to suppress inflammatory cytokine production.